2020
DOI: 10.1186/s40850-020-00059-1
|View full text |Cite
|
Sign up to set email alerts
|

Surrounding landscape influences the abundance of insect predators in rice field

Abstract: Background Natural enemy abundance in a crop plot depends on its prey presence and also influenced by habitats close to field. Landscape changes are also important factors driving pest and natural enemy population abundance in a specific crop field. Examining these kinds of effects on insect pests or biocontrol agents, as well as analysis of their functional food webs, would be asset to make a fruitful pest management programme at local scales. Therefore, this study was undertaken to evaluate the impact of sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Perennial non-crop habitats could provide nectar, pollen and alternative resources such as overwintering sites and refugees for antagonists. Speci cally, the proportion of non-crop area in the landscape has been positively related to species richness (Schmidt et al 2005), predators' abundance (Ali et al 2020;Gardiner et al 2009a) and subsequent suppression of pests as demonstrated in soybean (Gardiner, et al 2009b) and oilseed rape (Thies and Tscharntke 2010). Further case studies should provide a reliable conclusion about this issue.…”
Section: Discussionmentioning
confidence: 97%
“…Perennial non-crop habitats could provide nectar, pollen and alternative resources such as overwintering sites and refugees for antagonists. Speci cally, the proportion of non-crop area in the landscape has been positively related to species richness (Schmidt et al 2005), predators' abundance (Ali et al 2020;Gardiner et al 2009a) and subsequent suppression of pests as demonstrated in soybean (Gardiner, et al 2009b) and oilseed rape (Thies and Tscharntke 2010). Further case studies should provide a reliable conclusion about this issue.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, local women in Coatitilán, Mexico, perceive that forests and trees prevent soil erosion and that vegetation plays an important role in soil water retention and landscape structure maintenance, thereby protecting agricultural land and productivity [ 89 ]. For the mitigation of problems and to compensate for ecosystem service losses, a diverse complex landscape with natural habitats [ 88 ] can benefit farmers, such as in a form of pest control [ 44 ], or by receiving water for the rice fields from woodlots [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, landscape configuration and composition affect the ecological processes that occur in landscapes and landscape elements, such as hydrological flows and variation within catchments [ 42 ] or on the RAE’s arthropod population [ 43 ]. According to Ali et al (2020), the landscape around rice fields influences the insect pest population, indicating that landscape structure should be considered when implementing integrated pest management [ 44 ]. Similar effects have been reported in Sungai Semanok, Sarawak, where rice farmers lack access to the same high-quality pesticides as nearby oil palm plantations, resulting in pest migration to rice fields and thus negatively affecting agricultural productivity [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, agriculture has intensified at local and regional scales worldwide, increasing the proportion of monocultures, field sizes, and the degrees of fragmentation of natural and seminatural habitats, causing fundamental changes in agricultural landscapes (Tscharntke et al 2005;Baessler and Klotz 2006). These landscape changes are considered to be important factors modifying the abundances of both insect pest and natural enemy populations in agroecosystems (Ali et al 2020). However, a metaanalysis showed that crop pests and predators can also exhibit inconsistent responses to the composition of landscapes and that these responses might result from variations in how habitat and biocontrol are measured (Karp et al 2018).…”
Section: Introductionmentioning
confidence: 99%